Monte Carlo simulations of EBT3 film dose deposition for percentage depth dose (PDD) curve evaluation - Robinson, Spencer M. (J Appl Clin Med Phys, 2020)
PURPOSE: To use Monte Carlo (MC) calculations to evaluate the effects of Gafchromic EBT3 film orientation on percentage depth dose (PDD) curves. METHODS: Dose deposition in films placed in a water phantom, and oriented either parallel or perpendicular with respect to beam axis, were simulated with MC and compared to PDDs scored in a homogenous water phantom. The effects of introducing 0.01–1.00 mm air gaps on each side of the film as well as a small 1°‐3° tilt for film placed in parallel orientation were studied. PDDs scored based on two published EBT3 film compositions were compared. Three photon beam energies of 120 kVp, 220 kVp, and 6 MV and three field sizes between 1 × 1 and 5 × 5 cm(2) were considered. Experimental PDDs for a 6‐MV 3 × 3 cm(2) beam were acquired. RESULTS: PDD curves for films in perpendicular orientation more closely agreed to water PDDs than films placed in parallel orientation. The maximum difference between film and water PDD for films in parallel orientation was −12.9% for the 220 kVp beam. For the perpendicular film orientation, the maximum difference decreased to 5.7% for the 120 kVp beam. The inclusion of an air gap had the largest effect on the 6‐MV 1 × 1 cm(2) beam, for which the dose in the buildup region was underestimated by 21.2% compared to the simulation with no air gap. A 2° film tilt decreased the difference between the parallel film and homogeneous water phantom PDDs from −5.0% to −0.5% for the 6 MV 3 × 3 cm(2) beam. The “newer” EBT3 film composition resulted in larger PDD discrepancies than the previous composition. Experimental film data qualitatively agreed with MC simulations. CONCLUSIONS: PDD measurements with films should either be performed with film in perpendicular orientation to the beam axis or in parallel orientation with a ~ 2º tilt and no air gaps.